796Is Mindfulness a more effective intervention than Psychoeducation for reducing Bipolar Disorder-related symptoms of depression?. (2nd September 2021) - Bowe, Steven; Foley, Fiona; Fletcher, Kathryn; Thomas, Neil; Michalak, Erin; Berk, Lesley; Berk, Michael; Cotton, Sue; Engel, Lidia; Johnson, Sheri L.; Jones, Steven; Kyrios, Michael; et al.
Abstract: Background: The primary objective is to test the effectiveness of a novel online quality of life (QoL) intervention tailored for people with late stage (≥ 10 episodes) bipolar disorder (BD) compared with psychoeducation. Relative to early stage individuals, this late stage group may not benefit as much from existing psychosocial treatments. Methods: An NH&MRC funded international RCT to compare the effectiveness of two 5-week adjunctive online self-management interventions: Mindfulness for Bipolar 2.0 and an active control (Psychoeducation for Bipolar). A total of 300 participants were recruited primarily via social media channels. Evaluations occurred at pre- and post- treatment, and at 3- and 6- months follow-up. A secondary outcome measure was BD-related symptoms (depression). A longitudinal analysis was conducted using random effects mixed models. Results: Preliminary results suggest no change in mean QIDS_total over time ( p = 0.891 ). Nor does there appear to be a difference in groups ( B coeff = 0.47, 95%CI (-0.60, 1.55), p = 0.613 ) and no difference in intervention groups over time ( p = 0.828 ). Conclusions: The effectiveness of a novel QoL focused, mindfulness based, online guided self-help intervention for late stage BD does not appear to have been any more effective than a psychoeducation intervention for reducing depression. Key messages: There may be no significant benefit from using a mindfulness based, online guided self-help intervention over a psychoeducation intervention to reduce the BD symptoms of depression in late stage Bipolar disorder.